Micro-violence at work, a daily practice of the exercise of power of management in organizations - Román Muñoz, Olga Herminda (Sociedad y Economía, 2017)
The purpose of this research is to identify expressions of micro-violence at work that occur in different types of businesses, which constitute a daily practice of governance and control of the management of any organizational level. Through a perception survey that presents several expressions of micro-violence at work, it was determined that these practices are very common, and also go unnoticed because they are considered as "normal" within the organization. The above helps to generate and transmit more violence to the environment. From these results some thoughts for discussion in times of peace and reconciliation are exposed, from the duty of the management to forge a pleasant working environment for maintaining mental and physical health of their employees and to promote a comprehensive development of the organization under the principles of ethics and social responsibility.